2007
DOI: 10.1158/1078-0432.ccr-06-1461
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y–Dependent Cyclin B2 Expression in Colorectal Adenocarcinoma

Abstract: Purpose: Cyclin B2, a G 2 -M cyclin, is overexpressed in colorectal adenocarcinomas compared with the normal mucosa. This study examined the level of cyclin B2 overexpression according to the histologic findings and investigated the mechanism(s) and clinical implications of cyclin B2 overexpression in colorectal adenocarcinomas. Experimental Design: The immunoreactivity of the polyclonal antibodies to cyclin B2 was determined in colorectal cancer cells. The transcriptional regulation of cyclin B2 by NF-Y was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…Consistent with this finding, ccnb2-knockout mice, although develop normally, are smaller than normal mice and have reduced litter sizes, which suggests that cyclin B2 expression gives some growth advantage (16). Moreover, several studies have reported the accumulation of Cyclins B1 and B2 in human malignant tumors, such as colorectal and lung cancer (17)(18)(19)(20). Also, in human pituitary adenomas cyclins amplification and overexpression have been observed (21)(22)(23).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Consistent with this finding, ccnb2-knockout mice, although develop normally, are smaller than normal mice and have reduced litter sizes, which suggests that cyclin B2 expression gives some growth advantage (16). Moreover, several studies have reported the accumulation of Cyclins B1 and B2 in human malignant tumors, such as colorectal and lung cancer (17)(18)(19)(20). Also, in human pituitary adenomas cyclins amplification and overexpression have been observed (21)(22)(23).…”
Section: Introductionmentioning
confidence: 58%
“…Both B-type cyclins, in association with cdc2, play a critical role in regulating the G 2 -M phase transition of the cell cycle (15). Consistent with a general role in cell growth, several studies have reported the accumulation of cyclins B in human tumors, including pituitary adenomas (17)(18)(19)(20)(21)24). However, cyclin B2 involvement in pituitary tumorigenesis has not emerged yet, and the molecular mechanisms underlying its deregulation in cancer have not been definitively elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the present evidences of direct association between CCNB2 and GC progression are rare, CCNB2 may be another key regulator in GC development. At last, CCNB2 has been identified as a biomarker for the diagnosis of other cancers, such as lung cancer (Hofmann et al, 2004), colorectal cancer (Park et al, 2007) and cervical cancer (Garcia et al, 2013). These evidences suggest that CCNB2 may be a potential biomarker for diagnosis of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin B2 is one of essential components of the cell cycle regulatory machinery and has important roles in the control of the cell cycle at the G 2 -M-phase transition (32). The accumulation of cyclin B2 was also found in human malignant tumors (33)(34)(35). Cyclin E2 is a regulatory subunit of the CDK2 complex and accelerates the G 1 -S-phase transition (36).…”
Section: Discussionmentioning
confidence: 99%